2020
DOI: 10.1002/jum.15480
|View full text |Cite
|
Sign up to set email alerts
|

Fetoscopic Release of Amniotic Band Syndrome

Abstract: Amniotic band syndrome is a rare condition. There have been few cases reported of fetoscopic band dissection. The aim of this case series is to report 3 cases of fetoscopic treatment for amniotic band syndrome, including indication for surgery, technical aspects, complications and outcomes. Fetoscopic treatment was performed respectively at 23 5/7, 26 5/7 and 18 3/7 weeks' gestation. Two procedures were performed with a laser fiber through a single trocar whereas one surgery was performed with scissors. In con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 36 publications
0
17
0
2
Order By: Relevance
“…The results of fetoscopic amniotic band release in the limbs are encouraging. Extremity function was preserved in 75% of the published cases with detailed results reported 9,10 . The success rate here is related to preserving the extremity function.…”
Section: Discussionmentioning
confidence: 63%
“…The results of fetoscopic amniotic band release in the limbs are encouraging. Extremity function was preserved in 75% of the published cases with detailed results reported 9,10 . The success rate here is related to preserving the extremity function.…”
Section: Discussionmentioning
confidence: 63%
“…Recovery therapy following an intrauterine diagnosis of ABS has been reported. [37][38][39][40] A recent study showed that the fetoscopic release of an amniotic band using a laser and/or scissors effectively prevented the amputation of and dysfunctions in the fetal limbs and digits in cases of ABS 41 ; however, it was also associated with a risk of the premature rupture of membranes ranging from 38 to 57%. 40,42 However, fetoscopic amniotic band release surgery is technically difficult and the number of institutions capable of performing it is small.…”
Section: Discussionmentioning
confidence: 99%
“…There are case reports describing fetoscopic surgery in patients with ABS, with the intervention conferring a good prognosis [ 14 , 15 ]. However, fetoscopic surgery can cause complications such as uterine bleeding and preterm rupture of membranes.…”
Section: Discussionmentioning
confidence: 99%